SNAIL1 combines competitive displacement of ASCL2 and epigenetic mechanisms to rapidly silence the EPHB3 tumor suppressor in colorectal cancer. Issue 2 (16th September 2014) - Rönsch, Kerstin; Jägle, Sabine; Rose, Katja; Seidl, Maximilian; Baumgartner, Francis; Freihen, Vivien; Yousaf, Afsheen; Metzger, Eric; Lassmann, Silke; Schüle, Roland; Zeiser, Robert; Michoel, Tom; et al.
Abstract: EPHB3 is a critical cellular guidance factor in the intestinal epithelium and an important tumor suppressor in colorectal cancer (CRC) whose expression is frequently lost at the adenoma‐carcinoma transition when tumor cells become invasive. The molecular mechanisms underlying EPHB3 silencing are incompletely understood. Here we show that EPHB3 expression is anti‐correlated with inducers of epithelial‐mesenchymal transition (EMT) in primary tumors and CRC cells. In vitro, SNAIL1 and SNAIL2, but not ZEB1, repress EPHB3 reporter constructs and compete with the stem cell factor ASCL2 for binding to an E‐box motif. At the endogenous EPHB3 locus, SNAIL1 triggers the displacement of ASCL2, p300 and the Wnt pathway effector TCF7L2 and engages corepressor complexes containing HDACs and the histone demethylase LSD1 to collapse active chromatin structure, resulting in rapid downregulation of EPHB3. Beyond its impact on EPHB3, SNAIL1 deregulates markers of intestinal identity and stemness and in vitro forces CRC cells to undergo EMT with altered morphology, increased motility and invasiveness. In xenotransplants, SNAIL1 expression abrogated tumor cell palisading and led to focal loss of tumor encapsulation and the appearance of areas with tumor cells displaying a migratory phenotype. These changes were accompanied by loss of EPHB3 and CDH1 expression. Intriguingly, SNAIL1‐induced phenotypic changes of CRC cells are significantly impaired by sustained EPHB3 expression both in vitro and in vivo. Altogether, our results identify EPHB3 as a novel target of SNAIL1 and suggest that disabling EPHB3 signaling is an important aspect to eliminate a roadblock at the onset of EMT processes. Highlights: Expression of EPHB3 is anti‐correlated with inducers of EMT in colorectal cancer. EPHB3 is a direct target of the EMT inducer SNAIL1. SNAIL1 disables a transcriptional enhancer element to silence EPHB3. SNAIL1 displaces ASCL2 and engages epigenetic modifiers to disable the EPHB3 enhancer. Downregulation of EPHB3 eliminates a roadblock for the induction of EMT.